Forensic neuroscience: starting with understanding basic processes. Issue 1 (2nd January 2021) - Eisenbarth, Hedwig
ABSTRACT: Forensic Neuroscience can be misused in the individual assessment context, but it actually has a much more important contribution to make for criminal behaviour and the law. Using neuroscientific methods to understand the underlying pathways of criminal and violent behaviour on a broader level can be fruitful in determining targets for prevention and intervention. This review makes some suggestions how neuroscience can, and cannot, contribute to forensic psychology and the law by using them to question existing models of offending instead of using them for individual diagnostic attempts. Using the example of the presumed link between empathy and violent behaviour, it demonstrates how the use of neurophysiological measures, as well as experimental designs, is crucial for understanding if and how empathy and violence are linked as well as potential practical implications. Moving from assumptions based on correlational evidence to a better understanding of the brain could enrich existing approaches to offending treatment programs, but needs systematic approaches and desistance from use in individual cases.